2018
DOI: 10.14349/sumapsi.2018.v25.n2.5
|View full text |Cite
|
Sign up to set email alerts
|

Further considerations regarding PANAS: Contributions from four studies with different Argentinean samples

Abstract: In this research we analyzed the psychometric properties of the Positive and Negative Affect Schedule (PANAS) in samples coming from four independent studies: university students (Study 1, n = 392; Study 2, n = 395), general adult population (Study 3, n = 316), and athletes (Study 4, n = 533). Through confirmatory analyses we evaluated the following models: (a) two-factor model (Watson, Clark, & Tellegen, 1988), (b) three-factor model by Mehrabian (1997), (c) three-factor model by Gaudreau, Sánchez and Blondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…In addition, it has been shown in the previous PANAS history of applying CFAs (n = 27) that some items present a complex behavior (i.e., cross-load). This situation has been evidenced in six of the previous studies (22.22%), involving the items Alert, Excited, Strong, Nervous, Jittery, Hostile, and Active (Caicedo Cavagnis et al, 2018;Flores Kanter & Medrano, 2016;Heubeck & Boulter, 2020;Graudeau et al, 2006;Nunes et al, 2019). It is also relevant to note that in the remaining 11 studies that have used CFA (39.28%), only the fit of the two-factor model has been ascertained.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, it has been shown in the previous PANAS history of applying CFAs (n = 27) that some items present a complex behavior (i.e., cross-load). This situation has been evidenced in six of the previous studies (22.22%), involving the items Alert, Excited, Strong, Nervous, Jittery, Hostile, and Active (Caicedo Cavagnis et al, 2018;Flores Kanter & Medrano, 2016;Heubeck & Boulter, 2020;Graudeau et al, 2006;Nunes et al, 2019). It is also relevant to note that in the remaining 11 studies that have used CFA (39.28%), only the fit of the two-factor model has been ascertained.…”
mentioning
confidence: 93%
“…Within the ESEM models (n = 2), one of the antecedents has found better fit rates for the two-factor orthogonal solution (RMR = 0.04, RMSEA = 0.08; Carvalho et al, 2013), whereas another study found better fit for the three-factor solution (i.e., hierarchical model suggested by Mehrabian, 1997 1 ; over the 0.95 CFI criterion; Ortuño-Sierra et al, 2019). In the case of the CFA studies that have compared the fit of a two-factor model with other factor solutions (e.g., tree factor or bifactor models; n = 17), the same inconsistencies are observed, with six (35.29%) finding better fit for the threefactor model (i.e., suggested by Mehrabian, 1997or Gaudreau et al, 20062 Allan et al, 2015;Caicedo Cavagnis et al, 2018;Flores Kanter & Medrano, 2016;Merz et al, 2013;Ortuño-Sierra et al, 2015;Graudeau et al, 2006) and four (23.52%) reporting better fit for alternative hierarchical two-factor or bifactor models 3 (Leue & Beauducel, 2011;Mihić et al, 2014;Ortuño-Sierra et al, 2015;Seib-Pfeifer et al, 2017). It is important to mention that in the case of bifactor models, although they obtain higher fit indexes in most of the cases when they are applied, analysis of complementary rates has shown that these types of models present poor fit for the PANAS (see .…”
mentioning
confidence: 94%
“…In addition, it has been shown in the previous history of applying CFA (n = 27) that some items present a complex behavior (i.e., cross-load). This situation has been evidenced in 6 of the previous studies (22.22%), involving the items Alert, Excited, Strong, Nervous, Jittery, Hostile and Active (Caicedo-Cavagnis et al, 2018;Flores-Kanter & Medrano, 2016;Heubeck & Boulter, 2020;Graudeau et al, 2006;Nunes et al, 2019). It is also relevant to note that in the remaining 11 studies that have used CFA (39.28%), just the fit of the two-factor model has been verified.…”
Section: A Modern Network Approach To Revisiting the Positive And Negative Affective Schedule (Panas) Construct Validitymentioning
confidence: 84%
“…In the case of the CFAs who have compared the fit of a two-factor model considering other factor solutions (e.g., tree factor or bifactor models; n = 17), the same inconsistencies are observed, in which six (35.29%) find better fit for the three-factor model (i.e. suggested by Mehrabian, 1997or Gaudreau, Sanchez, & Blondin, 2006Allan et al, 2015;Caicedo-Cavagnis et al, 2018;Flores-Kanter & Medrano, 2016;Merz et al, 2013;Ortuño-Sierra et al, 2015;Graudeau et al, 2006); four (23.52%) report better fit in alternative hierarchical 2-factor or bifactor models 3 (Leue & Beauducel, 2011;Mihíc, Novović, Čolović, & Smederevac, 2014;Ortuño-Sierra et al, 2015;Seib-Pfeifer et al, 2017). It is important to mention that in the case of bifactor models, although they obtain higher fit indexes in most of the cases when they are applied, analysis of complementary rates has shown that these types of models present poor fit for the PANAS (see Flores-Kanter, Dominguez-Lara, Trógolo, & Medrano, 2018).…”
Section: A Modern Network Approach To Revisiting the Positive And Negative Affective Schedule (Panas) Construct Validitymentioning
confidence: 86%
See 1 more Smart Citation